Efficacy of nivolumab in pre-treated non-small-cell lung cancer patients harbouring KRAS mutations - Passiglia, Francesco (Br J Cancer, 2018)
BACKGROUND: The present study investigated the efficacy and safety of nivolumab in pre-treated patients with advanced NSCLC harbouring KRAS mutations. METHODS: Clinical data and KRAS mutational status were analysed in patients treated with nivolumab within the Italian Expanded Access Program. Objective response rate, progression-free survival and overall survival were evaluated. Patients were monitored for adverse events using the National Cancer Institute Common Terminology Criteria for Adverse Events. RESULTS: Among 530 patients evaluated for KRAS mutations, 206 (39%) were positive while 324 (61%) were KRAS wild-type mutations. KRAS status did not influence nivolumab efficacy in terms of ORR (20% vs 17%, P = 0.39) and DCR (47% vs 41%, P = 0.23). The median PFS and OS were 4 vs 3 months (P = 0.5) and 11.2 vs 10 months (P = 0.8) in the KRAS-positive vs the KRAS-negative group. The 3-months PFS rate was significantly higher in the KRAS-positive group as compared to the KRAS-negative group (53% vs 42%, P = 0.01). The percentage of any grade and grade 3–4 AEs were 45% vs 33% (P = 0.003) and 11% vs 6% (P = 0.03) in KRAS-positive and KRAS-negative groups, respectively. CONCLUSIONS: Nivolumab is an effective and safe treatment option for patients with previously treated, advanced non-squamous NSCLC regardless of KRAS mutations.